Inovasi Pembuatan Gropak Berbahan Dasar Sngkong pada Kelompok Dasawisma di Desa Sokaraja Tengah RT 2 RW 7 dalam Peluang Usaha Mandiri - Pusporini Palupi Jamaludin; Elizabeth Tika Kristina H; Paringsih Paringsih; Wahyu Nurul Waroh (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The importance of implementing Community Service (PKM) in the Tri Dharma of Higher Education can make a positive contribution to society. The implementation of this PKM is entitled "Innovation in Making Gropak Made from Cassava in the Dasawisma Group in Central Sokaraja Village RT 2 RW 7 in an Effort to Pioneer Independent Business Opportunities." This Community Service will be carried out on Jalan Sidodadi RT 2 RW 7 Sokaraja Tengah Banyumas. The method used in implementing PKM is a participatory approach, lectures, and an FGD (Focus Group Discussion) approach containing counseling on how to find out how to create greater space for women who want to try to develop themselves through productive efforts. Other benefits of women's empowerment through a creative economy by utilizing natural resources as an effort to empower women in improving the economy of dasawisma groups and village communities. Apart from that, it is hoped that with community service, the existence of universities can contribute to the development of the application of science to society. It is hoped that the knowledge gained in this community service will provide further insight into the use of natural potential to optimize the role of women, especially in improving the family economy so that women can be independent, especially in Sokaraja Tengah Village, Sokaraja Banyumas District, Central Java.